The link between corporate governance and corporate financial misconduct. A review of archival studies and implications for future research - Patrick Velte (Management Review Quarterly, 2021)
In this article, we review recent archival research articles (98 studies) on the impact of corporate governance on restatements, enforcement activities and fraud as corporate financial misconduct. Applying an agency-theoretical view, we mainly differentiate between four levels of corporate governance (group, individual, firm, and institutional level). We find that financial restatements on the one hand and the group and individual level of corporate governance on the other hand are dominant in our literature review. Enforcement actions and fraud events as misconduct proxies, and the firm and institutional level of corporate governance are of lower relevance yet. The following review highlights that many studies on corporate governance find inconclusive results on firms' financial misconduct. But there are indications that board expertise and especially gender diversity in the top management decreases firms' financial misconduct. We know very little about the impact of non-shareholder stakeholders' monitoring role on misconduct yet. In discussing potential future research, we emphasize the need for a more detailed analysis of misconduct proxies, recognition of moderator and especially mediator variables, especially in the interplay of the board of directors and external auditors.
Keywords: M41; M48; Q56; 650; Corporate financial misconduct; Corporate governance; Restatements; Enforcement; Board composition; Ownership structure